Multi-Drug Resistance Bacteria: A Case Study in Western Peninsular Malaysia Freshwaters - Mohd Suardi Suhaimi; Kam Kar Yern; Mohd Farizal Ahmad Kamaroddin; Syahidatul Fazlina Samsul Rizal; Syamimi Nadiah Baharudin; Fatin Shahira Binti Othman; Nur Roslina Peer Muhammad Hussain; Nurul Liyana Hassan; Nurul Aqidah Salikan; Nur Hidayah Mohd Dzukhi (Journal of Tropical Life Science, 2021)
The emergence of antibiotic resistant bacteria in aquatic environment has led to an increase in waterborne health risks to an alarming extent. This study attempts to investigate the population of certain antibiotic resistant strains in Peninsular Malaysia.Ã‚Â  From the samples of 14 rivers from 7 different states in Peninsular Malaysia, a total of 203 isolates were successfully isolated. These are from rivers in Negeri Sembilan, Melaka, Selangor, Kuala Lumpur, Kedah, Kelantan and Terengganu with 35, 15, 37, 39, 24, 26 and 27 isolates, respectively. The isolates were tested for their susceptibility towards 6 broad spectrum of antibiotics which are gentamicin, ampicillin, rifampicin, chloramphenicol, tetracycline, and ciprofloxacin. A total of 117 isolates were identified to have more than 20% MAR index value with 47 of the isolates possess minimum MAR index value of 50%. Based on MAR index value, 59% of isolates are high risk threats indicating a serious emergence of antibiotic resistant bacteria in the rivers in Peninsular Malaysia. Isolates with MAR index value of more than 50% were selected for 16S rRNA gene sequencing for further identification.Based on 16s rRNA gene sequencing, the isolates are a mixture of pathogenic and commensals bacteria. This also implies that the environment especially rivers can be a reservoir for genetic jugglery